A Re-Evaluation of the Relationship between Morphology and Pathogenicity in Candida Species - David Kadosh; Vasanthakrishna Mundodi (Journal of Fungi, 2020)
Many pathogenic Candida species possess the ability to undergo a reversible morphological transition from yeast to filamentous cells. In Candida albicans, the most frequently isolated human fungal pathogen, multiple lines of evidence strongly suggest that this transition is associated with virulence and pathogenicity. While it has generally been assumed that non-albicans Candida species (NACS) are less pathogenic than C. albicans, in part, because they do not filament as well, definitive evidence is lacking. Interestingly, however, a recent study suggests that filamentation of NACS is associated with reduced, rather than increased, pathogenicity. These findings, in turn, challenge conventional views and suggest that there are fundamental evolutionary differences in the morphology−pathogenicity relationship in C. albicans vs. NACS. The findings also raise many new and intriguing questions and open new avenues for future research, which are discussed.